Controlled drainage stabilized cotton yield by enhancing photosynthesis, the antioxidant defenses and osmoregulation at reduced nitrogen fertilization - Duan, Yonggang; Feng, Jiajia; Wang, Weihan; Liu, Shuaikang; Qi, Dongliang (Frontiers in Plant Science, 2026)
Controlled drainage (CD) can improve crop yield by optimizing the soil water and nutrient environment. Nevertheless, the combined effects of reduced nitrogen fertilization and CD on crop leaf senescence characteristics is unclear. Thus, a two-year field experiment was conducted to address the effects of nitrogen fertilizer rates (280, 252, 224, and 196 kg N ha-1, denoted as N1, N2, N3, and N4, respectively) on the leaf area index (LAI), SPAD value, net photosynthetic rate (Pn), activities of superoxide dismutase (SOD), peroxidases (POD), catalase (CAT), and the contents of soluble protein (SP) and malondialdehyde (MDA) in plant leaves, and the seed yield of cotton under CD and free drainage (FD). CD resulted in greater LAI, SPAD value, Pn, SOD, POD, and CAT activities, and SP content, and smaller MDA content at the three reduced nitrogen rates, and thus obtained a relatively high seed cotton yield. The delayed leaf senescence characteristics were due to greater soil moisture and NO3--N content in the plough (0–40 cm) layer under CD. Notably, all reduced nitrogen rates significantly decreased the cottonseed yield under FD, but N2 and N3 had comparable cottonseed yields under CD. Therefore, we concluded that controlled drainage could stabilize seed cotton yield by improving photosynthesis, the antioxidant defenses and osmoregulation at 80%-90% of normal nitrogen fertilizer rate. The results also reveal the physiological mechanisms through which the drainage regime mediates crop yield under varying nitrogen rates.